2009
DOI: 10.1177/082585970902500304
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Fentanyl as A Front-Line Approach to Moderate-Severe Pain: A meta-analysis of Randomized Clinical Trials

Abstract: Objective: The safety of transdermal fentanyl (TF) in comparison with slow-release oral morphine (SROM) in moderate-severe pain was assessed. Design: A systematic review of the literature was performed to identify all randomized trials comparing TF and SROM in moderate-severe pain. Overall safety was the primary end point. Trials enrolling both cancer and non-cancer patients were included in the analysis. Heterogeneity was assessed using the Mantel-Haenszel test; a random effects model was used for the pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Similar with European and American data [4-6], our data also showed that both transdermal fentanyl and sustained-release oral morphine were effective in treating stable moderate-severe cancer pain in Chinese population with less adverse effects for transdermal fentanyl. However, two differences should be pointed out.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar with European and American data [4-6], our data also showed that both transdermal fentanyl and sustained-release oral morphine were effective in treating stable moderate-severe cancer pain in Chinese population with less adverse effects for transdermal fentanyl. However, two differences should be pointed out.…”
Section: Discussionsupporting
confidence: 89%
“…Three systematic reviews of European and American literatures suggested both transdermal fentanyl and sustained-release oral morphine could effectively control moderate-severe cancer pain, but some adverse effects (mainly constipation) seemed to favor transdermal opiates in the preference of patients with moderate-severe cancer pain [4-6]. Our previous meta-analysis of 12 Chinese literatures also found similar result [7].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…TD-O administration provides a slow and steady increase in opiate plasma levels, extended half-lives of several days, and a long latent period before full pharmacologic effects are achieved. Based on the current literature available on the use of TD-Fe and transdermal buprenorphine (TD-Bu) for cancer pain, no significant differences in efficacy were discerned between the transdermal preparations in comparison to other opioids 11,12,18–20…”
Section: Td-os’ Place In Therapymentioning
confidence: 99%
“…A meta-analysis conducted by the same group of researchers found that cancer and non-cancer patients experienced significantly less constipation and urinary retention, as well as preferring the use of TD-Fe over PO SR morphine 12. No significant differences were discerned between PO SR opiates and TD-Os (TD-Fe and TD-Bu) in overall AE, overall gastrointestinal AE, overall neurologic AE, nausea, somnolence, hypoventilation, withdrawal from trial, and changes in opioid therapy 12…”
Section: Adverse Effects and Interactionsmentioning
confidence: 99%